Coronavirus and vulnerable people : addressing the divide in harm and responses and exploring implications for a more peaceful world - Finley, Laura L.; Hall, Pamela D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Drawing from many disciplinary areas, this edited volume explores how the Coronavirus pandemic has disproportionately harmed vulnerable and marginalized people in the U.S.. Chapters address harm to people of color that exacerbated structural racism and harm to low-wage workers that highlighted existing inequalities. In addition, the volume provides strategies that have been successful in mitigating these harms and recommendations for a post-pandemic more peaceful and just future."
Keywords: COVID-19 Pandemic, 2020-2023 -- Social aspects -- United States.; Minorities -- United States -- Social conditions.; Marginality, Social -- United States.; United States -- Social conditions -- 2020-; Health & Fitness -- Diseases & Conditions -- General.; Public health and preventive medicine.; Coping with, advice about illness and specific health conditions.; Popular medicine and health: the human body.; elektronické knihy; electronic books